Developing Communities of Praxis: Bridging the theory practice divide in teacher education - Anderson, Michael; Freebody, Kelly (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 2012)
Teacher education in universities is under pressure. In many new education policies there is a renewed focus on teacher quality, and therefore quality initial teacher education. In some countries this renewed focus has led to a resurgence of “alternative approaches” to teacher education such as Teach for America / Australia. One of the most persistent complaints about pre-service teacher education is that educational theory presented in these programs does not relate sufficiently to the real work of teachers. In an attempt to overcome these real or perceived divides, tertiary drama educators at the University of Sydney constructed a professional experience program based on both the community of practice model (Lave and Wenger, 1991) and Frierean notions of praxis (1972). The community of praxis approach emphasises the importance of integrating theory and practice to support the development of beginning teachers. This article outlines the development, implementation, and evaluation of this approach, including the reasoning behind its foundation and the theoretical and practical significance of such an approach for teacher-educators.